Sellar Chondroma Misdiagnosed as Craniopharyngioma: A Case Report - Chendong He; Wei Yang (Caucasian Medical Journal)
Tumors in the saddle area comprise a wide range of benign and malignant entities, with chondroma accounting for only a small fraction. There are only few reported cases in the literature. Sellar chondroma needs to be distinguished from pituitary adenoma, meningioma, craniopharyngioma, and chordoma, which is sometimes difficult to diagnose due to its rarity and overlap with other imaging findings. Moreover, it is easy to be misdiagnosed on imaging alone. Definitive diagnosis should depend on pathological findings. Despite being a benign tumor, saddle area chondroma poses a significant surgical challenge and is prone to complications due to its unique location, warranting attention from clinicians.